Chomp of the meat-eating vegetables - Cummings, Troy (New York, NY : Scholastic, Branches, 2014)
Alexander is used to finding monsters everywhere in Stermont, but now the school is being turned into an icebox by giant meat-eating vegetables--and his friend Rip has gone missing.
470
Keywords: Monsters -- Juvenile fiction; Elementary schools -- Juvenile fiction; Friendship -- Juvenile fiction; Horror tales; Monsters -- Fiction; Schools -- Fiction; Friendship -- Fiction; Horror stories; Horror fiction